“I believe it will not get worse”: A mixed-methods longitudinal study about patient's perspective of recently developed patellofemoral pain - Del Priore, Liliam Barbuglio [UNESP]; Briani, Ronaldo V. [UNESP]; Waiteman, Marina C. [UNESP]; Farinelli, Lucca André Liporoni Bego [UNESP]; Silva, Gleison Gustavo Moraes da [UNESP]; Silva, Théo Muniz de Souza Borges da [UNESP]; Glaviano, Neal; Azevedo, Fábio M. de [UNESP] (Elsevier, 2024)
Objectives: This study aimed to: (i) understand how women perceived their recently developed patellofemoral pain (PFP) regarding its cause, prognosis, and willingness to seek treatment; (ii) investigate self-reported function, knee-related quality of life (QoL), fear of movement, and physical activity level at the onset of PFP. Design: Mixed-methods longitudinal study. Setting: University. Participants: Sixty-eight pain-free women were followed up over one year. Main outcome measures: Those who developed PFP were interviewed within one month of the development of symptoms. Self-reported function, kinesiophobia, knee-related QoL, and physical activity were obtained at baseline and follow-up assessments. Results: Twenty-one women developed PFP. Most participants reported believing the increase in physical activity and/or sitting time was associated with the onset of PFP. Many reported believing symptoms would improve over time without any treatment. Only a small number of participants intended to seek care. Quantitatively, decreases in self-reported function and QoL, as well as increases in the physical activity level were observed after PFP development. Conclusion: Although decreases in self-reported function and QoL were observed, women reported believing their PFP is self-limiting and do not need treatment. Strategies to accurately disseminate knowledge about PFP are needed to help stimulating early care.
Keywords: Anterior knee pain; Early rehabilitation; Education; Health beliefs; Qualitative